2002
DOI: 10.1590/s0100-83582002000200012
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade e produtividade de sementes de canola (Brassica napus) após aplicação de dessecantes em pré-colheita

Abstract: A cultura de canola é indicada nos esquemas de rotação de culturas, bem como para diversificação agrícola e cobertura vegetal do solo no período de inverno na Região Sul do Brasil. Contudo, a colheita mecanizada é uma das operações mais críticas do sistema de produção, uma vez que os frutos do tipo síliqua apresentam maturação desuniforme, gerando grandes perdas de produtividade devido à deiscência natural. O uso de dessecantes químicos permite uma colheita com as síliquas em maturação mais uniforme, porém é i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
2
5
1
9
Order By: Relevance
“…These trends observed among means, corroborate with the study conducted by Motta et al (2007), that evaluating distinct periods of canola desiccating, ranging since periods near to the harvest up to the longest ones (0 to 54 days), observed that as longer the period before harvest, inferior the mass of a hundred seeds, as for instance, desiccation with periods really far from harvest may become damage to canola crop, not favor in such cases, the desiccating. For grain yield characteristic it was not observed significant differences (p≤0.05) among treatments (Figure 2), corroborating with data obtained by Marchiori et. al.…”
Section: Resultssupporting
confidence: 91%
“…These trends observed among means, corroborate with the study conducted by Motta et al (2007), that evaluating distinct periods of canola desiccating, ranging since periods near to the harvest up to the longest ones (0 to 54 days), observed that as longer the period before harvest, inferior the mass of a hundred seeds, as for instance, desiccation with periods really far from harvest may become damage to canola crop, not favor in such cases, the desiccating. For grain yield characteristic it was not observed significant differences (p≤0.05) among treatments (Figure 2), corroborating with data obtained by Marchiori et. al.…”
Section: Resultssupporting
confidence: 91%
“…Entretanto, adiantando-se a colheita, a haste estará verde e túrgida e, ao entrar no cilíndro da colhedora, este material será misturado às sementes, causando a elevação do teor de água, o que pode gerar problemas futuros no armazenamento (Marchiori Júnior et al 2002).…”
Section: Key-wordsunclassified
“…No entanto, apresenta amplo período de fl oração e consequente maturação desuniforme (MARCHIORI JR et al, 2002). O arranjo de plantas pode ser uma alternativa para se alcançar aumento da uniformidade de plantas, produção de grãos e óleo nesta espécie (MOMOH & ZHOU, 2001).…”
Section: Introductionunclassified